Nitrification in the Presence of Sulfide and Organic Matter in a Sequencing Moving Bed Biofilm Reactor (Smbbr) with Zeolite as Biomass Carrier - Huilinir-Curio, C; Montalvo-Martinez, S (John Wiley and Sons Ltd, 2020)
BACKGROUND: The biological nitrification process is inhibited in the presence of sulfide and organic matter (OM). The use of immobilized biomass on inert carriers may help to decrease this inhibition. Thus, the main goal of the present work was to develop a sequencing moving bed biofilm reactor (SMBBR) using zeolite as biomass carrier and to determine its performance in presence of sulfide and OM. RESULTS: The use of zeolite as biomass carrier improves both the total ammonia nitrogen (TAN) oxidation and nitrate accumulation, allowing the system to be able to treat higher nitrogen loading rates. The SMBBR with zeolite in presence of sulfide and OM performed nitrification better than a sequencing batch reactor (SBR), by keeping the TAN and chemical oxygen demand (COD) removal efficiency at >90% for both inhibitory conditions. The SMBBR also is able to degrade COD by ≤98%. Finally, biomass with zeolite settled faster than biomass without zeolite, improving the sludge volume index (SVI) by 53.8%. CONCLUSIONS: It was possible to develop a SMBBR system using zeolite as biomass carrier. The SMBBR could maintain a nitrifying system under inhibitory conditions, allowing efficiencies of TAN and COD removal as high as 90%. © 2019 Society of Chemical Industry. © 2019 Society of Chemical Industry